Digital Moral Philosophy of Leadership Simplicity: A Netnographic Study of Public Perception: Filsafat Moral Digital tentang Kesederhanaan Kepemimpinan: Studi Netnografi atas Persepsi Publik - Taufikin Taufikin; Budi Supriyatno; Ranowijaya (Universitas Indo Global Mandiri, 2026)
Purpose: This study aims to analyze the philosophical construction of leadership simplicity in the digital space through ontological, epistemological, and axiological perspectives. Design/methodology/approach: This study employs a qualitative, netnographic design. Data were collected from 518 public comments on Instagram posts from the @arsip.peristiwa account featuring figures of simple leadership, along with interaction data in the form of likes and shares. Purposive sampling was used to ensure data relevance. Analysis was conducted through thematic analysis combined with philosophical interpretation. Data validity was maintained through triangulation, audit trails, and critical reflection. Findings: Leadership simplicity is constructed in a multidimensional manner. Ontologically, simplicity is understood as the authentic essence of leadership. Epistemologically, knowledge about simplicity is shaped through collective memory, digital narratives, and social comparison. Axiologically, simplicity functions as a primary moral value, a tool for social critique, and a projection of future hopes. Practical Implications: For leaders and practitioners, simplicity must be managed not only as an internal value but also as a consistent public representation in the digital space. Originality/value: This study introduces the concept of the Digital Moral Ontology of Leadership Simplicity as a new theoretical contribution that expands understanding of leadership in the digital age, while also opening up new methodological approaches through the combination of netnography and philosophical analysis. Paper type: Research Paper